Sudden cardiac death in adults living with HIV: A systematic review - James Pierzchalski; Nance Cunnigham; Katherine Kooij; Silvia Guillemi; Reginald Smith; Lawrence McCandless; Robert Hogg (PLoS ONE, 2025)
Background People living with HIV (PLWH) have rising life expectancy, and robust evidence shows they are also at increased risk of cardiovascular disease. However, sudden cardiac death (SCD) for PLWH on antiretroviral therapy (ART) has received little attention. Our systematic review examines the quantitative adult PLWH SCD risk literature with a sub-focus of PLWH on ART. Methods We conducted systematic searches of PubMed, Embase, CENTRAL, CINAHL, Scopus, and Clinicaltrials.gov for peer-reviewed population studies using search terms “sudden cardiac death” AND (”HIV” OR “human immunodeficiency virus”) until 20 June 2025. Two reviewers analysed papers meeting eligibility criteria for their SCD classification methodology including for, but not limited to, comparability, generalizability, and misclassification biases including using the Newcastle-Ottawa Scale. Results The eight eligible studies included ~98 436 PLWH and demonstrated that males PLWH experience elevated SCD risk compared to the general population. One study with 97% male participants found a hazard ratio (HR) of 1.14 (95% CI: 1.04–1.25) for PLWH compared to non-PLWH. In another, comparing viral load groups of ≥500 vs < 500 found a HR of 1.33 (95% CI: 1.04–1.71) for PLWH with CD4 ≥ 500 compared to HIV-negative HR of 1.03 (95% CI: 0.90–1.18). An autopsy study’s male sex arm found a mortality rate ratio for PLWH compared to a reference of 1.34 (95% CI: 0.62–2.87). Conclusions The limited available research provides evidence that while SCD risk for male PLWH is elevated, maintaining HIV-RNA plasma viral load suppression and ≥200 CD4+ cells/mm 3 counts (ideally higher) likely lowers the risk of SCD to a rate that is approaching comparability to the general population. The risk of SCD in women living with HIV is still unknown, due to small sample sizes, as the majority of the participants in the PLWH studies were male.